Modified polytetrafluoroethylene and aqueous dispersion

By controlling the fracture strength and standard specific gravity of polytetrafluoroethylene and using modified monomers, the problem of high fracture strength but high extrusion pressure in the prior art is solved, and the combination of high fracture strength and low extrusion pressure is achieved, and the moldability is improved.

CN119654357APending Publication Date: 2025-03-18DAIKIN INDUSTRIES LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202380057994.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-08-10
Filing Date
2023-08-10
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The prior art is difficult to reduce the extrusion pressure of modified polytetrafluoroethylene while maintaining high fracture strength, affecting moldability.

Method used

By controlling the fracture strength and standard specific gravity of polytetrafluoroethylene, combined with the use of modified monomers such as vinylidene fluoride, modified polytetrafluoroethylene with a fracture strength greater than 32.8N and a standard specific gravity of more than 2.150 was prepared.

Benefits of technology

Modified polytetrafluoroethylene, which has a high fracture strength but a low extrusion pressure, is achieved, and the moldability is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005262146760000051
    Figure BDA0005262146760000051
  • Figure BDA0005262146760000052
    Figure BDA0005262146760000052
  • Figure BDA0005262146760000241
    Figure BDA0005262146760000241
Patent Text Reader

Abstract

Provided are a modified polytetrafluoroethylene and an aqueous dispersion which have a low extrusion pressure despite high breaking strength. The breaking strength of the modified polytetrafluoroethylene is larger than 32.8 N, and the standard specific gravity is 2.150 or above.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to modified polytetrafluoroethylene and aqueous dispersion. Background Art

[0002] When polytetrafluoroethylene is highly stretched in the unfired state, a porous polytetrafluoroethylene membrane can be obtained. This porous membrane allows gases such as water vapor to pass through, but due to the strong water repellency of polytetrafluoroethylene, water droplets cannot pass through. This unique property is used in clothing, separation membranes, etc.

[0003] Patent Document 1 describes a fine powder composed of a tetrafluoroethylene homopolymer having a predetermined standard specific gravity and breaking strength.

[0004] Patent Document 2 describes a modified polytetrafluoroethylene having units based on perfluoro(propyl vinyl ether) and hexafluoropropylene.

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: Japanese Patent Application Publication No. 2002-201217

[0008] Patent Document 2: Japanese Patent Application Publication No. 2006-117912 Summary of the invention

[0009] Technical problem to be solved by the invention

[0010] The object of the present invention is to provide a modified polytetrafluoroethylene and an aqueous dispersion which have a low extrusion pressure despite high breaking strength.

[0011] Solutions to technical problems

[0012] The present invention (1) is a modified polytetrafluoroethylene having a breaking strength greater than 32.8N and a standard specific gravity greater than 2.150.

[0013] The present invention (2) is the modified polytetrafluoroethylene described in the present invention (1), wherein the strength ratio represented by breaking strength (N) / extrusion pressure (MPa) is greater than 1.90 N / MPa.

[0014] The present invention (3) is the modified polytetrafluoroethylene described in the present invention (1) or (2), wherein the breaking strength is greater than 37.0N.

[0015] The present invention (4) is a modified polytetrafluoroethylene in combination with any one of the present inventions (1) to (3), wherein the standard specific gravity is 2.155 or more.

[0016] The present invention (5) is a modified polytetrafluoroethylene in combination with any one of the present inventions (1) to (4), wherein the standard specific gravity is 2.160 or more.

[0017] The present invention (6) is a modified polytetrafluoroethylene having a standard specific gravity of 2.150 or more and a strength ratio represented by breaking strength (N) / extrusion pressure (MPa) of more than 1.90 N / MPa.

[0018] The present invention (7) is a modified polytetrafluoroethylene comprising tetrafluoroethylene units and vinylidene fluoride units, wherein the amount of the vinylidene fluoride units is 1.0% by mass or less based on all polymerized units.

[0019] The present invention (8) is a modified polytetrafluoroethylene in combination with any one of the present inventions (1) to (7), which is in the form of a powder.

[0020] The present invention (9) is a modified polytetrafluoroethylene in combination with any one of the present inventions (1) to (8), which is in the form of a fine powder.

[0021] The present invention (10) is an aqueous dispersion comprising particles of modified polytetrafluoroethylene in combination with any one of the present inventions (1) to (7).

[0022] Effects of the Invention

[0023] According to the present invention, it is possible to provide a modified polytetrafluoroethylene and an aqueous dispersion having a low extrusion pressure despite high breaking strength. DETAILED DESCRIPTION

[0024] Generally, when the extrusion pressure of polytetrafluoroethylene (PTFE) is increased, the breaking strength can be increased, but the paste extrudate becomes hard and the moldability of the extrudate tends to deteriorate.

[0025] However, as a result of intensive research, it was found that, contrary to common technical knowledge, PTFE having a high breaking strength but a low extrusion pressure can be obtained by using modified PTFE and controlling the breaking strength and standard specific gravity.

[0026] The present invention is described in detail below.

[0027] The present invention provides a modified PTFE (hereinafter also referred to as a first modified PTFE) having a breaking strength greater than 32.8N and a standard specific gravity of 2.150 or more.

[0028] Since the first modified PTFE has the above-mentioned structure, it has a low extrusion pressure despite its high breaking strength and is excellent in moldability.

[0029] Its reason is still unclear, but infers: standard specific gravity height (molecular weight is low) can give molding with flexibility, even under low extrusion pressure, also can be molded uniformly.In addition, by being modified PTFE, compared with homopolymerization PTFE, when paste is extruded, fibrillated molecule combines more closely, can obtain high fracture strength.

[0030] The first modified PTFE has a breaking strength greater than 32.8 N. The breaking strength is preferably greater than 33.0 N, more preferably greater than 35.0 N, further preferably greater than 37.0 N, further preferably greater than 37.0 N, further preferably greater than 38.0 N, particularly preferably greater than 40.0 N, and most preferably greater than 42.0 N. The higher the breaking strength, the better, and it may be less than 100.0 N, less than 80.0 N, or less than 50.0 N.

[0031] The above-mentioned breaking strength is a value obtained by the following method.

[0032] The tensile bar (made by stretching a bar) obtained in the following tensile test performed at a tensile speed of 100% / sec was clamped and fixed in a movable jaw with a gauge length of 5.0 cm, and a tensile test was performed at 25°C at a speed of 300 mm / min, and the strength at break was measured as the breaking strength.

[0033] The standard specific gravity (SSG) of the first modified PTFE is 2.150 or more. From the perspective of being able to further improve the breaking strength and further reduce the extrusion pressure, the standard specific gravity is preferably 2.155 or more, more preferably 2.160 or more, more preferably 2.165 or more, further more preferably 2.170 or more, particularly preferably 2.175 or more, and most preferably 2.180 or more, and is preferably 2.250 or less, more preferably 2.240 or less, further preferably 2.230 or less, further more preferably 2.220 or less, and particularly preferably 2.210 or less.

[0034] The standard specific gravity is measured by a water displacement method according to ASTM D 792 using a sample molded according to ASTM D 4895.

[0035] The strength ratio represented by the breaking strength (N) / extrusion pressure (MPa) of the first modified PTFE is preferably greater than 1.90 N / MPa, more preferably 1.95 N / MPa or more, further preferably 2.00 N / MPa or more, further more preferably 2.05 N / MPa or more, further more preferably 2.10 N / MPa or more, further more preferably 2.20 N / MPa or more, and particularly preferably 2.25 N / MPa or more. The higher the strength ratio, the better, and it can be 5.00 N / MPa or less, or 4.00 N / MPa or less.

[0036] A higher strength ratio means a higher breaking strength and a lower extrusion pressure.

[0037] The above-mentioned breaking strength is a value obtained by the above-mentioned method.

[0038] The extrusion pressure is a value obtained by the following method.

[0039] 21.7 g of lubricant (trade name: Isopar H (registered trademark), manufactured by Exxon) was added to 100 g of modified PTFE powder, and mixed at room temperature for 3 minutes to obtain a PTFE fine powder mixture. Next, the obtained PTFE fine powder mixture was placed at room temperature (25°C) for at least 1 hour before extrusion, and then paste extruded through a hole (diameter 2.5 mm, land length 11 mm, introduction angle 30°) at room temperature with a reduction ratio of 100:1 (ratio of the cross-sectional area of ​​the inlet of the die to the cross-sectional area of ​​the outlet) to obtain a uniform beading (extruded molded body). The extrusion speed, i.e., the punch speed, was set to 20 inches / minute (51 cm / minute). The extrusion pressure is a value obtained by measuring the load when the extrusion load reaches a balanced state in the paste extrusion and dividing it by the cross-sectional area of ​​the barrel used in the paste extrusion.

[0040] The first modified PTFE is preferably stretchable. In this specification, "stretchable" is determined by the following criteria.

[0041] The strips obtained by extruding the above paste are dried at 230°C for 30 minutes, and the lubricant is removed from the strips. Next, the strips (extruded molded bodies) are cut into appropriate lengths, and each end is fixed to the chucks in a manner that the chuck spacing is 2.0 inches (51 mm), and heated to 300°C in an air circulation oven. Next, the chucks are separated at the desired speed (stretching speed) to a separation distance equivalent to the desired stretching (total stretching), and a stretching test is performed. This stretching method is essentially in accordance with the method disclosed in the specification of U.S. Patent No. 4,576,869, except that the extrusion speed (51 cm / minute instead of 84 cm / minute) is different. "Stretching" refers to the increase in length caused by extension, and is usually expressed in relation to the original length. In the above-mentioned production method, the above-mentioned stretching speed is 1000% / second, and the above-mentioned total stretching is 2400%. The situation in which there is no breakage until the above-mentioned stretching is completed is judged to be able to stretch.

[0042] The modified PTFE of the present invention is preferably not broken even after the stretching is completed when a stretching test is conducted under the conditions of a stretching speed of 100% / sec and a total stretching of 2400% in the above-mentioned production method.

[0043] The first modified PTFE includes polymerized units based on tetrafluoroethylene (TFE) (TFE units) and polymerized units based on a modifying monomer (modified monomer units). In this specification, "modified PTFE" refers to PTFE in which the content of the modifying monomer units is 1.0 mass % or less relative to all polymerized units.

[0044] The content of the TFE unit in the modified PTFE may be 99.0% by mass or more.

[0045] The modified PTFE may be composed only of TFE units and modified monomer units.

[0046] The content of the modified monomer unit is 1.0% by mass or less relative to the total polymerized units. From the perspective of further reducing the extrusion pressure and further improving the breaking strength, the content of the modified monomer unit is preferably 0.80% by mass or less, more preferably 0.50% by mass or less, further preferably 0.40% by mass or less, further more preferably 0.30% by mass or less, further more preferably 0.20% by mass or less, further more preferably 0.10% by mass or less, further more preferably 0.08% by mass or less, particularly preferably 0.05% by mass or less, and most preferably 0.03% by mass or less.

[0047] The content of the modified monomer unit may be 0.0001% by mass or more, 0.001% by mass or more, or 0.005% by mass or more, based on the total polymerized units.

[0048] In the present specification, the modified monomer unit refers to a part of the molecular structure of the modified PTFE and is a part derived from the modified monomer.

[0049] The content of each polymerized unit described above can be calculated by appropriately combining NMR, FT-IR, elemental analysis, and fluorescent X-ray analysis according to the type of monomer.

[0050] As the above-mentioned modifying monomer, there is no particular limitation as long as it can be copolymerized with TFE, and examples thereof include perfluoroolefins such as hexafluoropropylene [HFP]; hydrogen-containing fluoroolefins such as trifluoroethylene and vinylidene fluoride [VDF]; perhaloolefins such as chlorotrifluoroethylene; perfluorovinyl ether; perfluoroallyl ether; (perfluoroalkyl)ethylene, ethylene, etc. In addition, the modifying monomer used may be one kind or two or more kinds.

[0051] The perfluorovinyl ether is not particularly limited, and examples thereof include the following general formula (A):

[0052] CF2=CF-ORf(A)

[0053] (wherein Rf represents a perfluoro organic group) and the like. In this specification, the above-mentioned "perfluoro organic group" refers to an organic group in which all hydrogen atoms bonded to carbon atoms are replaced by fluorine atoms. The above-mentioned perfluoro organic group may have an ether oxygen.

[0054] Examples of the perfluorovinyl ether include perfluoro(alkyl vinyl ether) [PAVE] wherein Rf in the general formula (A) is a perfluoroalkyl group having 1 to 10 carbon atoms. The perfluoroalkyl group preferably has 1 to 5 carbon atoms.

[0055] Examples of the perfluoroalkyl group in PAVE include a perfluoromethyl group, a perfluoroethyl group, a perfluoropropyl group, a perfluorobutyl group, a perfluoropentyl group, and a perfluorohexyl group.

[0056] As the perfluorovinyl ether, further examples include those in which Rf in the general formula (A) is a perfluoro(alkoxyalkyl) group having 4 to 9 carbon atoms, and Rf is the following formula:

[0057] [Chemistry 1]

[0058]

[0059] (wherein m represents 0 or an integer of 1 to 4), and Rf is the following formula:

[0060] [Chemistry 2]

[0061]

[0062] (wherein n represents an integer of 1 to 4) and the like.

[0063] The (perfluoroalkyl)ethylene (PFAE) is not particularly limited, and examples thereof include (perfluorobutyl)ethylene (PFBE) and (perfluorohexyl)ethylene.

[0064] Examples of perfluoroallyl ethers include those of general formula (B):

[0065] CF2=CF-CF2-ORf 1 (B)

[0066] (Where Rf 1 represents a perfluorinated organic group).

[0067] The above Rf 1Preferred are perfluoroalkyl groups having 1 to 10 carbon atoms or perfluoroalkoxyalkyl groups having 1 to 10 carbon atoms. As the perfluoroallyl ether, at least one selected from the group consisting of CF2=CF-CF2-O-CF3, CF2=CF-CF2-O-C2F5, CF2=CF-CF2-O-C3F7, and CF2=CF-CF2-O-C4F9 is preferred, at least one selected from the group consisting of CF2=CF-CF2-O-C2F5, CF2=CF-CF2-O-C3F7, and CF2=CF-CF2-O-C4F9 is more preferred, and CF2=CF-CF2-O-CF2CF3 is further preferred.

[0068] As the above-mentioned modifying monomer, from the aspect of easily making the breaking strength and standard specific gravity within the above-mentioned range, at least one selected from the group consisting of VDF, CTFE, PAVE and HFP is preferred, at least one selected from the group consisting of VDF, CTFE and HFP is more preferred, and at least one selected from the group consisting of VDF and HFP is further preferred. From the aspect of further reducing the extrusion pressure and further improving the breaking strength, and from the aspect of obtaining high breaking strength and breaking elongation even when processed at low temperature, VDF is particularly preferred.

[0069] From the viewpoint of improving heat resistance, it is also preferable to use both VDF and HFP as the above-mentioned modifying monomer.

[0070] The first modified PTFE generally has non-melt secondary processability. The non-melt secondary processability refers to the property that the melt flow rate cannot be measured at a temperature higher than the melting point according to ASTM D-1238 and D-2116, in other words, the property that it is not easy to flow even in the melting temperature range.

[0071] When the first modified PTFE does not have a history of being heated to a temperature of 300°C or higher, in a melting heat curve when the temperature is increased at a rate of 10°C / min using a differential scanning calorimeter [DSC], one or more endothermic peaks preferably appear in the range of 333 to 347°C, and the melting heat of 290 to 350°C calculated from the above melting heat curve is 62 mJ / mg or higher.

[0072] The first modified PTFE can be produced, for example, by a production method including the step (A) of emulsion polymerizing TFE and a modifying monomer.

[0073] The above-mentioned emulsion polymerization can be carried out in an aqueous medium in the presence of an anionic fluorinated surfactant and a polymerization initiator, for example.

[0074] The emulsion polymerization can be carried out as follows: an aqueous medium, the anionic fluorinated surfactant, a monomer, and other additives as needed are added to a polymerization reactor, the contents of the reactor are stirred, the reactor is maintained at a predetermined polymerization temperature, and then a predetermined amount of a polymerization initiator is added to initiate the polymerization reaction. After the polymerization reaction starts, monomers, polymerization initiators, chain transfer agents, and the surfactant can be added according to the purpose.

[0075] From the aspect of easily obtaining the above-mentioned various physical properties, it is preferred that the concentration of the modified monomer (preferably VDF) in the gas in the reactor at the start of polymerization (when the initiator is added) is set to 0.001 mol% or more, and more preferably 0.01 mol% or more. In addition, the above-mentioned concentration can be 15 mol% or less, preferably 6.0 mol% or less, more preferably 5.0 mol% or less, and further more preferably 3.0 mol% or less, and particularly preferably 1.0 mol% or less. The above-mentioned modified monomer concentration can be maintained thereafter until the end of the polymerization reaction, or pressure relief can be implemented midway. The above-mentioned modified monomer is preferably added once before the start of polymerization, but a portion can also be added continuously or intermittently after the start of polymerization.

[0076] As the above-mentioned polymerization initiator, there is no particular limitation as long as it can generate free radicals in the polymerization temperature range, and known oil-soluble and / or water-soluble polymerization initiators can be used. Furthermore, it is also possible to combine with a reducing agent etc. to initiate polymerization in a redox form. The concentration of the above-mentioned polymerization initiator is appropriately determined according to the type of monomer, the molecular weight of the target modified PTFE, and the reaction rate.

[0077] As the polymerization initiator, an oil-soluble radical polymerization initiator or a water-soluble radical polymerization initiator can be used.

[0078] The oil-soluble free radical polymerization initiator may be a known oil-soluble peroxide, and for example, the following peroxides may be cited as representative substances: dialkyl peroxycarbonates such as diisopropyl peroxydicarbonate and di-sec-butyl peroxydicarbonate; peroxyesters such as tert-butyl peroxyisobutyrate and tert-butyl peroxypivalate; dialkyl peroxides such as di-tert-butyl peroxide; and di(ω-hydro-dodecafluoroheptanoyl) peroxide, di(ω-hydro-tetradecafluoroheptanoyl) peroxide, di(ω-hydro-hexadecanoyl) peroxide, di(perfluorobutanoyl) peroxide, di(perfluoropentanoyl) peroxide, di(perfluorohexanoyl) peroxide, di(perfluoroheptanoyl) peroxide, di(perfluorooctanoyl) peroxide. peroxide, di(perfluorononanoyl)peroxide, di(ω-chloro-hexafluorobutyryl)peroxide, di(ω-chloro-decafluorohexanoyl)peroxide, di(ω-chloro-tetrafluorooctanoyl)peroxide, ω-hydro-dodecafluoroheptanoyl-ω-hydrohexafluorononanoyl-peroxide, ω-chloro-hexafluorobutyryl-ω-chloro-decafluorohexanoyl-peroxide, ω-hydro-dodecafluoroheptanoyl-perfluorobutyryl-peroxide, di(dichloropentafluorobutyryl)peroxide, di(trichlorooctafluorohexanoyl)peroxide, di(tetrachloroundecanoyl)peroxide, di(pentachlorotetrafluorodecanoyl)peroxide, di(undecanotridodecanoyl)peroxide and the like di[perfluoro(or fluorochloro)acyl]peroxides; and the like.

[0079] As the water-soluble free radical polymerization initiator, it can be a known water-soluble peroxide, for example, ammonium salts, potassium salts, sodium salts of persulfuric acid, perboric acid, perchloric acid, perphosphoric acid, percarbonic acid, tert-butyl peroxymaleate, tert-butyl hydroperoxide, etc. It can also contain a reducing agent such as sulfites and sulfites, and its amount can be 0.1 to 20 times that of the peroxide.

[0080] For example, when the polymerization is carried out at a low temperature below 30°C, it is preferred to use a redox initiator that combines an oxidant and a reductant as a polymerization initiator. As the oxidant, persulfates, organic peroxides, potassium permanganate, manganese triacetate, ammonium cerium nitrate, bromates, etc. can be mentioned. As the reductant, sulfites, bisulfites, bromates, diimides, oxalic acid, etc. can be mentioned. As persulfates, ammonium persulfate and potassium persulfate can be mentioned. As sulfites, sodium sulfite and ammonium sulfite can be mentioned. In order to increase the decomposition rate of the initiator, it is also preferred to add copper salts and iron salts to the combination of redox initiators. As copper salts, copper (II) sulfate can be mentioned, and as iron salts, iron (II) sulfate can be mentioned.

[0081] As the redox initiator, it is preferred that the oxidizing agent is permanganic acid or a salt thereof, persulfate, manganese triacetate, cerium (IV) salt, or bromic acid or a salt thereof, and the reducing agent is dicarboxylic acid or a salt thereof, or diimine.

[0082] More preferably, the oxidizing agent is permanganic acid or a salt thereof, persulfate, or bromic acid or a salt thereof, and the reducing agent is a dicarboxylic acid or a salt thereof.

[0083] Examples of the redox initiator include combinations of potassium permanganate / oxalic acid, potassium permanganate / ammonium oxalate, manganese triacetate / oxalic acid, manganese triacetate / ammonium oxalate, cerium ammonium nitrate / oxalic acid, and cerium ammonium nitrate / ammonium oxalate.

[0084] When a redox initiator is used, either the oxidant or the reductant may be placed in a polymerization vessel in advance, and then the other may be added continuously or intermittently to initiate polymerization. For example, when potassium permanganate / ammonium oxalate is used, it is preferred that ammonium oxalate is placed in the polymerization vessel and potassium permanganate is continuously added thereto.

[0085] It should be noted that, in the redox initiator of the present specification, when "potassium permanganate / ammonium oxalate" is described, it means a combination of potassium permanganate and ammonium oxalate. The same applies to other compounds.

[0086] The redox initiator is particularly preferably a combination of an oxidizing agent which is a salt and a reducing agent which is a salt.

[0087] For example, the oxidizing agent as the salt is more preferably at least one selected from the group consisting of persulfate, permanganate, cerium (IV) salt and bromate, further preferably permanganate, and particularly preferably potassium permanganate.

[0088] The reducing agent for the salt is more preferably at least one selected from the group consisting of oxalates, malonates, succinates, glutarates and bromates, further preferably oxalates, and particularly preferably ammonium oxalate.

[0089] Specifically, the redox initiator is preferably at least one selected from the group consisting of potassium permanganate / oxalic acid, potassium permanganate / ammonium oxalate, potassium bromate / ammonium sulfite, manganese triacetate / ammonium oxalate and cerium ammonium nitrate / ammonium oxalate, more preferably at least one selected from the group consisting of potassium permanganate / oxalic acid, potassium permanganate / ammonium oxalate, potassium bromate / ammonium sulfite and cerium ammonium nitrate / ammonium oxalate, and further preferably potassium permanganate / oxalic acid.

[0090] When a redox initiator is used, the oxidant and the reducing agent may be added at once at the beginning of the polymerization, the reducing agent may be added at once and the oxidant may be added continuously at the beginning of the polymerization, the oxidant may be added at once and the reducing agent may be added continuously at the beginning of the polymerization, or both the oxidant and the reducing agent may be added continuously.

[0091] When a redox initiator is used as a polymerization initiator, the amount of the oxidant added is preferably 5 ppm or more, more preferably 10 ppm or more, and preferably 10000 ppm or less, and more preferably 1000 ppm or less, relative to the aqueous medium. The amount of the reducing agent added is preferably 5 ppm or more, more preferably 10 ppm or more, and preferably 10000 ppm or less, and more preferably 1000 ppm or less.

[0092] From the aspect of easily obtaining modified PTFE suitable for stretching purposes, the addition amount of the oxidant is preferably 0.1 ppm or more, more preferably 1.0 ppm or more, and preferably 100 ppm or less, and more preferably 10 ppm or less, relative to the aqueous medium. The addition amount of the reducing agent is preferably 0.1 ppm or more, more preferably 1.0 ppm or more, and preferably 100 ppm or less, and more preferably 10 ppm or less.

[0093] When a redox initiator is used in the emulsion polymerization, the polymerization temperature is preferably 100°C or lower, more preferably 95°C or lower, and further preferably 90°C or lower. It is preferably 10°C or higher, more preferably 20°C or higher, and further preferably 30°C or higher.

[0094] As the polymerization initiator, a water-soluble radical polymerization initiator and a redox initiator are preferred because the breaking strength and the standard specific gravity can be easily adjusted to fall within the above ranges.

[0095] The amount of polymerization initiator added is not particularly limited, and the amount (for example, a concentration of several ppm relative to water) added at the initial stage of polymerization once, successively, or continuously to the extent that the polymerization rate does not significantly decrease is sufficient. The upper limit is the range in which the heat of polymerization can be used to remove heat from the device surface and the reaction temperature can be increased at the same time, and the more preferred upper limit is the range in which the heat of polymerization can be removed from the device surface. More specifically, for example, relative to an aqueous medium, it is preferably more than 1 ppm, more preferably more than 10 ppm, and further preferably more than 50 ppm. In addition, it is preferably less than 100000 ppm, more preferably less than 10000 ppm, and further preferably less than 5000 ppm.

[0096] From the perspective of easily obtaining the above-mentioned physical properties, the amount of the polymerization initiator added is preferably an amount equivalent to 0.1 ppm or more, more preferably an amount equivalent to 1.0 ppm or more, and is preferably an amount equivalent to 100 ppm or less, more preferably an amount equivalent to 10 ppm or less, relative to the aqueous medium.

[0097] The aqueous medium is a reaction medium for polymerization and is a liquid containing water. The aqueous medium is not particularly limited as long as it contains water, and may contain water and a non-fluorinated organic solvent such as alcohol, ether, or ketone and / or a fluorinated organic solvent having a boiling point of 40° C. or less.

[0098] In the emulsion polymerization, a nucleating agent, a chain transfer agent, a buffer, a pH adjuster, a stabilizing aid, a dispersion stabilizer, a radical scavenger, a decomposing agent of a polymerization initiator, and the like may be used as necessary.

[0099] The emulsion polymerization is preferably carried out by adding a nucleating agent for the purpose of adjusting the particle size. The nucleating agent is preferably added before the start of the polymerization reaction.

[0100] As the nucleating agent, a known nucleating agent can be used, and for example, at least one selected from the group consisting of fluoropolyethers, nonionic surfactants, and chain transfer agents is preferred, and a nonionic surfactant is more preferred.

[0101] Examples of the fluorinated polyether include perfluoropolyether (PFPE) acid and salts thereof.

[0102] The above-mentioned perfluoropolyether (PFPE) acid or its salt may have any chain structure in which oxygen atoms in the main chain of the molecule are separated by saturated fluorocarbon groups having 1 to 3 carbon atoms. In addition, two or more fluorocarbon groups may exist in the molecule. A representative structure has a repeating unit represented by the following formula.

[0103] (-CFCF3-CF2-O-) n

[0104] (-CF2-CF2-CF2-O-) n

[0105] (-CF2-CF2-O-) n -(-CF2-O-) m

[0106] (-CF2-CFCF3-O-) n -(-CF2-O-) m

[0107] These structures are described by Kasai in J. Appl. Polymer Sci. 57, 797 (1995). As disclosed in the document, the PFPE acid or its salt may have a carboxylic acid group or its salt at one or both ends. In addition, the PFPE acid or its salt may have a sulfonic acid, phosphonic acid group or its salt at one or both ends. In addition, the PFPE acid or its salt may have different groups at each end. For monofunctional PFPE, the other end of the molecule is usually perfluorinated and may also contain hydrogen or chlorine atoms. The PFPE acid or its salt has at least 2 ether oxygens, preferably at least 4 ether oxygens, and more preferably at least 6 ether oxygens. Preferably, at least one of the fluorocarbon groups separated by the ether oxygen, more preferably at least two of such fluorocarbon groups have 2 or 3 carbon atoms. More preferably, at least 50% of the fluorocarbon groups separated by the ether oxygen have 2 or 3 carbon atoms. In addition, preferably, the PFPE acid or its salt has a total of at least 15 carbon atoms, for example, the preferred minimum value of n or n+m in the repeating unit structure is at least 5. Two or more PFPE acids or salts thereof having an acid group at one or both ends can be used in the production method of the present invention. The PFPE acid or salt thereof preferably has a number average molecular weight of less than 6000 g / mol.

[0108] From the aspect that the modified PTFE can be further high molecular weighted and the stretchability can be improved, the above-mentioned emulsion polymerization is preferably carried out by adding a free radical scavenger or a decomposition agent of a polymerization initiator. The above-mentioned free radical scavenger or the decomposition agent of a polymerization initiator is preferably added after the polymerization reaction starts, preferably before 10% by mass or more, preferably 20% by mass or more of the total TFE consumed in the polymerization reaction is polymerized, and in addition, preferably before 50% by mass or less, preferably 40% by mass or less is polymerized. In the case of performing the pressure relief and re-pressurization described later, it is preferably added afterwards.

[0109] As the free radical scavenger, a compound that is added to the free radical in the polymerization system or has no reinitiation ability after chain transfer is used. Specifically, a compound having the following functions is used: it is easy to undergo a chain transfer reaction with a primary free radical or a growing free radical, and then generate a stable free radical that does not react with the monomer, or it is easy to undergo an addition reaction with a primary free radical or a growing free radical to generate a stable free radical.

[0110] The activity of a substance generally referred to as a chain transfer agent is characterized by a chain transfer constant and a reinitiation efficiency. Among chain transfer agents, a substance having a reinitiation efficiency of substantially 0% is referred to as a free radical scavenger.

[0111] The radical scavenger can be, for example, a compound whose chain transfer constant with TFE at the polymerization temperature is greater than the polymerization rate constant and whose reinitiation efficiency is substantially zero%. "Substantially zero% reinitiation efficiency" means that the generated radicals make the radical scavenger a stable radical.

[0112] Preferred are compounds having a chain transfer constant (Cs) with TFE at the polymerization temperature (=chain transfer rate constant (kc) / polymerization rate constant (kp)) greater than 0.1, and the chain transfer constant (Cs) of the above-mentioned compound is more preferably 0.5 or more, further preferably 1.0 or more, further preferably 5.0 or more, and particularly preferably 10 or more.

[0113] The radical scavenger is preferably at least one selected from the group consisting of, for example, aromatic hydroxy compounds, aromatic amines, N,N-diethylhydroxylamine, quinone compounds, terpenes, thiocyanates, and cupric chloride (CuCl 2 ).

[0114] Examples of the aromatic hydroxy compound include unsubstituted phenol, polyphenol, salicylic acid, m-salicylic acid or p-salicylic acid, gallic acid, and naphthol.

[0115] Examples of the unsubstituted phenol include o-nitrophenol, m-nitrophenol, p-nitrophenol, o-aminophenol, m-aminophenol, p-aminophenol, p-nitrosophenol, etc. Examples of the polyphenol include catechol, resorcinol, hydroquinone, pyrogallol, pyrogallol, naphthol resorcinol, etc.

[0116] Examples of the aromatic amines include o-phenylenediamine, m-phenylenediamine, p-phenylenediamine, and benzidine.

[0117] Examples of the quinone compound include o-benzoquinone, m-benzoquinone, p-benzoquinone, 1,4-naphthoquinone, and alizarin.

[0118] Examples of the thiocyanate include ammonium thiocyanate (NH4SCN), potassium thiocyanate (KSCN), and sodium thiocyanate (NaSCN).

[0119] As the radical scavenger, an aromatic hydroxy compound is preferred, an unsubstituted phenol or a polyphenol is more preferred, and hydroquinone is further preferred.

[0120] From the aspect of appropriately reducing the standard specific gravity, the amount of the free radical scavenger added is preferably an amount equivalent to 3% to 500% (molar basis) of the polymerization initiator concentration. A more preferred lower limit is 10% (molar basis), and a further preferred upper limit is 400% (molar basis), and a further preferred upper limit is 300% (molar basis).

[0121] As the decomposition agent of the above-mentioned polymerization initiator, any compound capable of decomposing the polymerization initiator used may be used, for example, at least one selected from the group consisting of sulfites, bisulfites, bromates, diimides, diimide salts, oxalic acid, oxalates, copper salts and iron salts is preferred. As sulfites, sodium sulfite and ammonium sulfite can be cited. As copper salts, copper (II) sulfate can be cited, and as iron salts, iron (II) sulfate can be cited.

[0122] From the aspect of appropriately reducing the standard specific gravity, the amount of the above-mentioned decomposition agent added is preferably an amount equivalent to 3% to 500% (molar basis) of the initiator concentration. A more preferred lower limit is 10% (molar basis), and a further preferred upper limit is 400% (molar basis), and a further preferred upper limit is 300% (molar basis).

[0123] In the above-mentioned emulsion polymerization, the polymerization temperature and polymerization pressure are appropriately determined according to the type of monomer used, the molecular weight of the target modified PTFE, and the reaction rate. Usually, the polymerization temperature is 5°C to 150°C, preferably above 10°C, more preferably above 30°C, and further preferably above 50°C. In addition, it is more preferably below 120°C, and further preferably below 100°C.

[0124] The polymerization pressure is 0.05 MPaG to 10 MPaG. The polymerization pressure is more preferably 0.3 MPaG or more, and even more preferably 0.5 MPaG or more. Furthermore, the polymerization pressure is more preferably 5.0 MPaG or less, and even more preferably 3.0 MPaG or less.

[0125] In the emulsion polymerization, after the modified monomer is added to the polymerization vessel, it is preferred not to release the pressure before the polymerization is completed. This allows the modified monomer to remain in the system until the end of the polymerization, and can further improve the breaking strength of the obtained modified PTFE.

[0126] The production method may include a step (B) of subjecting the aqueous dispersion to precipitation to obtain a wet powder of the modified PTFE. The precipitation may be performed by a known method.

[0127] The manufacturing method may include a step (C) of drying the wet powder. The drying is usually carried out by vacuum, high frequency, hot air or the like while keeping the wet powder in a state where it is not too fluid, preferably in a static state. Friction between powders, especially at high temperatures, usually has an adverse effect on fine powder PTFE. This is because the particles composed of PTFE have the property of simply fibrillating even when subjected to a small shear force, thereby losing the originally stable particle structure.

[0128] The drying temperature is preferably 300°C or lower, more preferably 250°C or lower, further preferably 230°C or lower, still more preferably 210°C or lower, still more preferably 190°C or lower, and particularly preferably 170°C or lower, from the perspective of reducing the extrusion pressure. From the perspective of improving the breaking strength, it is preferably 10°C or higher, more preferably 100°C or higher, further preferably 150°C or higher, further more preferably 170°C or higher, further more preferably 190°C or higher, and particularly preferably 210°C or higher. In order to further improve the strength ratio, it is preferably adjusted appropriately within this temperature range.

[0129] The present invention also provides a modified PTFE (hereinafter also referred to as second modified PTFE) having a standard specific gravity of 2.150 or more and a strength ratio represented by breaking strength (N) / extrusion pressure (MPa) of more than 1.90 N / MPa.

[0130] Since the second modified PTFE has the above-mentioned structure, it has a low extrusion pressure despite its high breaking strength and is excellent in moldability.

[0131] The standard specific gravity (SSG) of the second modified PTFE is 2.150 or more. From the perspective of being able to further improve the breaking strength and further reduce the extrusion pressure, the standard specific gravity is preferably 2.155 or more, more preferably 2.160 or more, more preferably 2.165 or more, further more preferably 2.170 or more, particularly preferably 2.175 or more, and most preferably 2.180 or more, and is preferably 2.250 or less, more preferably 2.240 or less, further preferably 2.230 or less, further more preferably 2.220 or less, and particularly preferably 2.210 or less.

[0132] The strength ratio represented by the breaking strength (N) / extrusion pressure (MPa) of the second modified PTFE is greater than 1.90 N / MPa, preferably 1.95 N / MPa or more, more preferably 2.00 N / MPa or more, further preferably 2.05 N / MPa or more, further more preferably 2.10 N / MPa or more, further more preferably 2.20 N / MPa or more, and particularly preferably 2.25 N / MPa or more. The higher the strength ratio, the better, and it can be 5.00 N / MPa or less, or 4.00 N / MPa or less.

[0133] The breaking strength of the second modified PTFE is preferably greater than 32.8 N, more preferably greater than 33.0 N, further preferably greater than 35.0 N, further more preferably greater than 37.0 N, further more preferably greater than 37.0 N, further more preferably greater than 38.0 N, particularly preferably greater than 40.0 N, and most preferably greater than 42.0 N. The higher the breaking strength, the better, and it can be 100.0 N or less, 80.0 N or less, or 50.0 N or less.

[0134] The second modified PTFE is preferably stretchable.

[0135] The second modified PTFE comprises TFE units and modified monomer units. Examples of the modified monomers include those exemplified in the first modified PTFE. The content of the modified monomer units may be in the same range as that of the first modified PTFE.

[0136] The second modified PTFE may have the same physical properties as the first modified PTFE except that the strength ratio is higher than 1.90 N / MPa.

[0137] The second modified PTFE can be produced by the production method described in connection with the first modified PTFE.

[0138] The present invention also provides a modified PTFE (hereinafter also referred to as the third modified PTFE) comprising tetrafluoroethylene (TFE) units and vinylidene fluoride (VDF) units, wherein the amount of the VDF units is 1.0 mass % or less based on all polymerized units.

[0139] Since the third modified PTFE has the above-mentioned structure, it has a low extrusion pressure despite its high breaking strength and is excellent in moldability.

[0140] In addition, the third modified PTFE has high fracture strength and elongation at break even when processed at low temperatures. When using modified monomers such as perfluoro(alkyl vinyl ether) and hexafluoropropylene, when the processing (e.g., sintering) temperature is reduced, the fracture strength and elongation at break also decrease, but when VDF units are used as modified monomers, surprisingly, high fracture strength and elongation at break can be obtained even when processed at low temperatures (e.g., below 340°C).

[0141] The content of the VDF unit is 1.0% by mass or less relative to the total polymerized units, and is preferably 0.80% by mass or less, more preferably 0.50% by mass or less, further preferably 0.40% by mass or less, still more preferably 0.30% by mass or less, still more preferably 0.20% by mass or less, still more preferably 0.10% by mass or less, still more preferably 0.08% by mass or less, particularly preferably 0.05% by mass or less, and most preferably 0.03% by mass or less, relative to the total polymerized units, from the viewpoint of further reducing the extrusion pressure and further improving the breaking strength.

[0142] The content of the VDF unit may be 0.0001% by mass or more, 0.001% by mass or more, or 0.005% by mass or more, based on the total polymerized units.

[0143] In this specification, the VDF unit refers to a part of the molecular structure of the modified PTFE and is a part derived from VDF.

[0144] The content of the TFE units in the third modified PTFE may be 99.0% by mass or more.

[0145] The third modified PTFE may be composed of only TFE units and VDF units, or may contain polymerized units based on other modifying monomers other than VDF (other modifying monomer units) together with TFE units and VDF units.

[0146] Examples of the other modifying monomer include the modifying monomers exemplified in the first modified PTFE. Among them, HFP is preferred from the viewpoint of improving heat resistance.

[0147] When the second modified PTFE contains the above-mentioned other modifying monomer units, the total amount of the VDF units and the above-mentioned other modifying monomer units is preferably 1.0% by mass or less based on the total polymerized units.

[0148] It is one of the preferred embodiments that the second modified PTFE contains TFE units, VDF units, and HFP units, and the total amount of the VDF units and the HFP units is 1.0% by mass or less based on all polymerized units.

[0149] The breaking strength of the third modified PTFE is preferably greater than 32.8 N, more preferably 33.0 N or more, further preferably 35.0 N or more, further more preferably 37.0 N or more, further more preferably greater than 37.0 N, further more preferably 38.0 N or more, particularly preferably 40.0 N or more, and most preferably 42.0 N or more. The higher the breaking strength, the better, and it can be 100.0 N or less, 80.0 N or less, or 50.0 N or less.

[0150] From the perspective of being able to further improve the breaking strength and further reduce the extrusion pressure, the standard specific gravity (SSG) of the third modified PTFE is preferably 2.150 or more, more preferably 2.155 or more, further preferably 2.160 or more, even more preferably 2.165 or more, even more preferably 2.170 or more, particularly preferably 2.175 or more, and most preferably 2.180 or more. In addition, it is preferably 2.250 or less, more preferably 2.240 or less, further preferably 2.230 or less, even more preferably 2.220 or less, and particularly preferably 2.210 or less.

[0151] The strength ratio represented by the breaking strength (N) / extrusion pressure (MPa) of the third modified PTFE is preferably greater than 1.90 N / MPa, more preferably 1.95 N / MPa or more, further preferably 2.00 N / MPa or more, further more preferably 2.05 N / MPa or more, further more preferably 2.10 N / MPa or more, further more preferably 2.20 N / MPa or more, and particularly preferably 2.25 N / MPa or more. The higher the strength ratio, the better, and it can be 5.00 N / MPa or less, or 4.00 N / MPa or less.

[0152] The third modified PTFE is preferably stretchable.

[0153] The third modified PTFE may have the same physical properties as the first modified PTFE except that the modifying monomer is VDF.

[0154] The third modified PTFE can be produced by using VDF as a modifying monomer in the production method described for the first modified PTFE.

[0155] The first, second and third modified PTFE are preferably in the form of powder, more preferably in the form of fine powder.

[0156] The first, second and third modified PTFE can also be provided in the form of an aqueous dispersion. An aqueous dispersion containing particles of any one of the first, second and third modified PTFE is also a preferred embodiment of the present invention. Using the aqueous dispersion of the present invention, a coating film that is not prone to cracking can be generated.

[0157] The average primary particle size of the first, second and third modified PTFE is preferably 500 nm or less, more preferably 350 nm or less, further preferably 300 nm or less, particularly preferably 280 nm or less, and is preferably 100 nm or more, more preferably 150 nm or more, further preferably 170 nm or more, particularly preferably 200 nm or more.

[0158] The above average primary particle size is measured by the following method.

[0159] The modified PTFE aqueous dispersion was diluted with water until the solid content concentration reached 0.15% by mass, and the transmittance of the projected light at 550 nm relative to the unit length of the obtained diluted emulsion was measured, and the number-based length average particle size determined by measuring the directional diameter using a transmission electron microscope photograph was prepared to prepare a calibration curve. Using this calibration curve, the number average particle size was determined from the measured transmittance of the projected light at 550 nm of each sample as the average primary particle size.

[0160] The average aspect ratio of the primary particles of the first, second and third modified PTFEs may be 2.0 or less, preferably 1.8 or less, more preferably 1.7 or less, further preferably 1.6 or less, further preferably 1.5 or less, further preferably 1.4 or less, particularly preferably 1.3 or less, particularly preferably 1.2 or less, and most preferably 1.1 or less. In addition, the average aspect ratio may be 1.0 or more.

[0161] The average aspect ratio is determined by observing fluororesin powder or an aqueous fluororesin dispersion diluted to a solid content concentration of about 1% by mass using a scanning electron microscope (SEM), performing image processing on 200 or more particles randomly selected, and calculating the average ratio of the major axis to the minor axis.

[0162] The average secondary particle size of the first, second and third modified PTFE is preferably 100 μm or more, more preferably 200 μm or more, further preferably 300 μm or more, and is preferably 2000 μm or less, more preferably 1000 μm or less, further preferably 800 μm or less, and particularly preferably 700 μm or less.

[0163] The above average secondary particle size is measured in accordance with JIS K6891.

[0164] The first, second and third modified PTFEs are particularly useful as raw materials for stretched bodies. A stretched body formed from any of the first, second and third modified PTFEs is also a preferred embodiment of the present invention.

[0165] The stretched product can be obtained by stretching the first, second and third modified PTFEs.

[0166] The stretched body is also preferably in the shape of a film, a tube, a fiber, or a rod.

[0167] When the stretched body is a film (stretched film or porous film), it can be stretched by a known PTFE stretching method.

[0168] Preferably, a sheet-shaped or rod-shaped paste extrudate is roll-stretched in the extrusion direction to obtain a uniaxially stretched film.

[0169] Furthermore, by stretching in the width direction using a tenter or the like, a biaxially stretched film can also be obtained.

[0170] It is also preferred to perform a semi-firing treatment before stretching.

[0171] The stretched body can be made into a porous body with high porosity, and can be suitably used as a filter material for various microfiltration filters such as air filters and reagent filters, a supporting material for polymer electrolyte membranes, and the like.

[0172] Furthermore, the present invention is also useful as a material for products used in the fields of fibers, medicine, electrochemistry, sealing materials, air filtration, ventilation / internal pressure regulation, liquid filtration, and general consumables.

[0173] Specific uses are exemplified below.

[0174] Electrochemical field

[0175] Dielectric material prepreg, EMI shielding material, heat transfer material, etc. More specifically, printed circuit board, electromagnetic shielding material, insulating heat transfer material, insulating material, etc.

[0176] Sealing material field

[0177] Gaskets, sealing pads, pump diaphragms, pump tubes, sealing materials for aircraft, etc.

[0178] Air filtration field

[0179] ULPA filter (for semiconductor manufacturing), HEPA filter (for hospital and semiconductor manufacturing), cylindrical cartridge filter (for industrial use), bag filter (for industrial use), heat-resistant bag filter (for exhaust gas treatment), heat-resistant pleated filter (for exhaust gas treatment), SINBRAN filter (for industrial use), catalytic filter (for exhaust gas treatment), filter with adsorbent (for HDD assembly), ventilation filter with adsorbent (for HDD assembly), ventilation filter (for HDD assembly, etc.), filter for vacuum cleaner (for vacuum cleaner), general-purpose multilayer felt, cartridge filter for GT (for GT interchangeable parts), cooling filter (for electronic equipment housing), etc.

[0180] Ventilation / internal pressure adjustment area

[0181] Freeze-drying materials such as freeze-drying containers, automotive ventilation materials suitable for electronic circuits or lamps, container uses such as container covers, protective ventilation uses for electronic devices including small terminals such as tablet terminals and mobile phone terminals, medical ventilation uses, etc.

[0182] Liquid filtration field

[0183] Semiconductor liquid filters (for semiconductor manufacturing), hydrophilic PTFE filters (for semiconductor manufacturing), filters suitable for chemicals (for reagent processing), filters for pure water production lines (for pure water production), backwash type liquid filtration filters (for industrial wastewater treatment), etc.

[0184] General consumables field

[0185] Clothing, cable guide tubes (removable wires suitable for motorcycles), motorcycle clothing, cast pads (medical protective gear), vacuum cleaner filters, bagpipes (musical instruments), cables (signal cables for guitars, etc.), strings (for stringed instruments), etc.

[0186] Fiber field

[0187] PTFE fiber (fibrous material), sewing thread (fabric), knitting thread (fabric), rope, etc.

[0188] Medical field

[0189] Embedded products (stretchable products), artificial blood vessels, catheters, general surgery (tissue reinforcement materials), head and neck products (dura mater substitutes), oral health (tissue regeneration medicine), plastic surgery (bandages), etc.

[0190] The first, second and third modified PTFEs can also be suitably used as various additives such as dustproof additives, drip-proof agents, adhesives for batteries, for coating purposes, and for glass cloth impregnation processing purposes.

[0191] In addition, the aqueous dispersion containing particles of the first, second and third modified PTFE is used to manufacture infiltration bodies such as roofing materials by impregnating them in surface coating agents for cooking utensils, glass fibers, carbon fibers, Kebler (registered trademark) fibers, etc., and is also used in the formation of films formed by coating and firing on a coated object in applications such as high-frequency printed substrates, conveyor belts, and sealing gaskets, and can be applied to various applications.

[0192] Although the embodiments have been described above, it should be understood that various changes may be made to the embodiments and details without departing from the spirit and scope of the claims.

[0193] Example

[0194] Next, the present invention will be described in more detail with reference to Examples, but the present invention is not limited to these Examples.

[0195] Various physical properties were measured by the following methods.

[0196] Polymer solid content

[0197] 1 g of the modified PTFE aqueous dispersion was dried in a blower dryer at 150° C. for 60 minutes, and the ratio of the mass of the heating residue to the mass of the aqueous dispersion (1 g) was expressed as a percentage.

[0198] Content of modified monomer

[0199] The VDF content is determined by the following method. 19In addition, the PTFE powder was molded into a film disk, and the infrared absorbance at 1429 cm was obtained based on the infrared absorbance measured by FT-IR. -1 / 2360cm -1 The absorbance ratio of 19 The measured values ​​of F-NMR and the absorbance ratio are used to prepare a calibration curve, and the VDF content is calculated from the calibration curve.

[0200] The HFP content was determined by FT-IR measurement of infrared absorbance at 982 cm-1 obtained by compression molding a film disk made of PTFE powder. -1 Absorbance / 935cm -1 It is calculated by multiplying the absorbance ratio by 0.3.

[0201] The CTFE content was determined by FT-IR measurement of infrared absorbance at 957 cm-1 obtained by compression molding a film disk made of PTFE powder. -1 Absorbance / 2360cm -1 The absorbance ratio is multiplied by 0.58.

[0202] Standard Specific Gravity (SSG)

[0203] The measurement was performed by the water displacement method according to ASTM D 792 using a sample formed according to ASTM D 4895.

[0204] Average primary particle size

[0205] The modified PTFE aqueous dispersion was diluted with water until the solid content concentration reached 0.15% by mass, and the transmittance of the projected light at 550 nm relative to the unit length of the obtained diluted emulsion was measured, and the number-based length average particle size determined by measuring the directional diameter using a transmission electron microscope photograph was prepared to prepare a calibration curve. Using this calibration curve, the number average particle size was determined from the measured transmittance of the projected light at 550 nm of each sample as the average primary particle size.

[0206] Extrusion pressure

[0207] 21.7 g of lubricant (trade name: Isopar H (registered trademark), manufactured by Exxon) was added to 100 g of modified PTFE powder, and mixed at room temperature for 3 minutes to obtain a PTFE fine powder mixture. Next, the obtained PTFE fine powder mixture was placed at room temperature (25°C) for at least 1 hour before extrusion, and then paste extruded through a hole (diameter 2.5 mm, land length 11 mm, introduction angle 30°) at room temperature with a reduction ratio of 100:1 (ratio of the cross-sectional area of ​​the inlet of the die to the cross-sectional area of ​​the outlet) to obtain a uniform beading (extruded molded body). The extrusion speed, i.e., the punch speed, was set to 20 inches / minute (51 cm / minute). The extrusion pressure is a value obtained by measuring the load when the extrusion load reaches a balanced state in the paste extrusion and dividing it by the cross-sectional area of ​​the barrel used in the paste extrusion.

[0208] Tensile test

[0209] The strips extruded from the paste are heated at 230°C for 30 minutes to remove the lubricant from the strips. Next, the strips (extruded molded bodies) are cut into appropriate lengths, each end is fixed to the chucks at intervals of 2.0 inches (51 mm) between the chucks, and heated to 300°C in an air circulating oven. Next, the chucks are separated at the desired speed (stretching speed) to a separation distance corresponding to the desired stretching (total stretching), and a stretching test is performed. This stretching method is essentially in accordance with the method disclosed in the specification of U.S. Patent No. 4,576,869, except that the extrusion speed (51 cm / min instead of 84 cm / min) is different. "Stretching" refers to the increase in length caused by extension, and is usually expressed in relation to the original length. In the above-mentioned production method, the above-mentioned stretching speed is 100% / sec, and the above-mentioned total stretching is 2400%.

[0210] Breaking strength

[0211] The tensile bar obtained in the above tensile test (made by stretching a bar) was clamped and fixed in movable jaws with a gauge length of 5.0 cm, and a tensile test was performed at 25°C and a speed of 300 mm / min. The strength at break was measured as the breaking strength.

[0212] Strength ratio

[0213] Calculated from breaking strength (N) / extrusion pressure (MPa).

[0214] Synthesis example 1

[0215] A white solid A was obtained by the method described in Synthesis Example 1 of International Publication No. 2021 / 045228.

[0216] Example 1

[0217] 3600g of deionized water, 180g of paraffin, 5.4g of white solid A, and 0.0265g of oxalic acid were added to a SUS reactor with a stirrer having a content of 6L. Then, the contents of the reactor were heated to 70°C while being sucked, and tetrafluoroethylene (TFE) was purged to remove oxygen in the reactor, and the contents were stirred. 1.70g of vinylidene fluoride (VDF) was pressed into the reactor with TFE, and then TFE was added to make it 2.70MPaG. A potassium permanganate aqueous solution in which 3.4mg of potassium permanganate was dissolved in deionized water was continuously added to the reactor as an initiator. After the initiator was injected, a decrease in pressure occurred, and the start of polymerization was observed. TFE was added to the reactor, and the pressure was kept constant at 2.70MPaG. At the moment when the amount of TFE fed reached 430g, the potassium permanganate aqueous solution was stopped. At the moment when the amount of TFE fed reached 1815g, the supply of TFE was stopped, stirring was stopped, and the reaction was terminated. After that, the pressure in the reactor was vented to normal pressure, nitrogen replacement was performed, and the contents were taken out of the reactor and cooled. The paraffin was removed to obtain a PTFE aqueous dispersion. The obtained PTFE aqueous dispersion had a solid content concentration of 33.3% by mass and an average primary particle size of 251 nm.

[0218] The obtained PTFE aqueous dispersion was diluted to a solid content concentration of 13% by mass, and vigorously stirred in a container with a stirrer to solidify. The solidified wet powder was taken out and dried at 210°C for 18 hours to obtain PTFE powder. Various physical properties of the obtained PTFE powder were measured. The results are shown in Table 1.

[0219] Example 2

[0220] The polymerization was carried out under the same conditions as in Example 1 except that the VDF feed amount was changed to 0.4 g, the potassium permanganate of 3.4 mg was changed to 5.6 mg, and the feed of the potassium permanganate aqueous solution was stopped when the TFE feed amount reached 870 g. The solid content concentration of the obtained PTFE aqueous dispersion was 33.4% by mass, and the average primary particle size was 263 nm.

[0221] Using the obtained PTFE aqueous dispersion, a PTFE powder was obtained in the same manner as in Example 1. Various physical properties of the obtained PTFE powder were measured. The results are shown in Table 1.

[0222] Example 3

[0223] The same conditions as in Example 1 were used except that the amount of VDF added was changed to 2.56 g, potassium permanganate was changed to 3.7 mg, and stirring was stopped when the amount of TFE added reached 430 g, the pressure in the polymerization kettle was reduced to atmospheric pressure, TFE was introduced to a pressure of 2.7 MPaG, and stirring was restarted. The obtained PTFE aqueous dispersion had a solid content concentration of 33.9 mass % and an average primary particle size of 246 nm.

[0224] Using the obtained PTFE aqueous dispersion, a PTFE powder was obtained in the same manner as in Example 1. Various physical properties of the obtained PTFE powder were measured. The results are shown in Table 1.

[0225] Example 4

[0226] Polymerization was carried out under the same conditions as in Example 1 except that the amount of VDF charged was changed to 32.0 g and 3.4 mg of potassium permanganate was changed to 3.9 mg. The solid content concentration of the obtained PTFE aqueous dispersion was 33.5% by mass and the average primary particle size was 224 nm.

[0227] Using the obtained PTFE aqueous dispersion, a PTFE powder was obtained in the same manner as in Example 1. Various physical properties of the obtained PTFE powder were measured. The results are shown in Table 1.

[0228] Example 5

[0229] 3600g of deionized water, 180g of paraffin wax, and 5.4g of white solid A were added to a 6L SUS reactor with a stirrer. Then, the contents of the reactor were heated to 80°C while being sucked, and tetrafluoroethylene (TFE) was purged to remove oxygen in the reactor, and the contents were stirred. 5.82g of vinylidene fluoride (VDF) was pressed into the reactor with TFE, and then TFE was added to make it 2.70MPaG. An aqueous solution of 7.2mg of ammonium persulfate (APS) dissolved in deionized water was added to the reactor as an initiator. After the initiator was injected, a pressure drop occurred, and the start of polymerization was observed. TFE was added to the reactor, and the pressure was kept constant at 2.70MPaG. At the moment when the amount of TFE fed reached 430g, an aqueous solution of 36.0mg of hydroquinone dissolved in deionized water was added. At the moment when the amount of TFE fed reached 1580g, the supply of TFE was stopped, stirring was stopped, and the reaction was terminated. After that, the pressure in the reactor was vented to normal pressure, nitrogen was replaced, and the contents were taken out of the reactor and cooled. The paraffin was removed to obtain a PTFE aqueous dispersion. The obtained PTFE aqueous dispersion had a solid content concentration of 30.2% by mass and an average primary particle size of 214 nm.

[0230] The obtained PTFE aqueous dispersion was diluted to a solid content concentration of 13% by mass, and vigorously stirred in a container with a stirrer to solidify. The solidified wet powder was taken out and dried at 210°C for 18 hours to obtain PTFE powder. Various physical properties of the obtained PTFE powder were measured. The results are shown in Table 1.

[0231] Example 6

[0232] Polymerization was carried out under the same conditions as in Example 5 except that the VDF feed amount was changed to 3.1 g and the hydroquinone feed amount was changed to 18.2 mg to obtain a PTFE aqueous dispersion. The obtained PTFE aqueous dispersion had a solid content concentration of 30.3% by mass and an average primary particle size of 223 nm.

[0233] Using the obtained PTFE aqueous dispersion, a PTFE powder was obtained in the same manner as in Example 5. Various physical properties of the obtained PTFE powder were measured. The results are shown in Table 1.

[0234] Example 7

[0235] Polymerization was carried out under the same conditions as in Example 5 except that the amount of VDF charged was changed to 0.19 g and the amount of hydroquinone charged was changed to 11.0 mg to obtain a PTFE aqueous dispersion. The obtained PTFE aqueous dispersion had a solid content concentration of 30.3% by mass and an average primary particle size of 265 nm.

[0236] Using the obtained PTFE aqueous dispersion, a PTFE powder was obtained in the same manner as in Example 5. Various physical properties of the obtained PTFE powder were measured. The results are shown in Table 1.

[0237] Example 8

[0238] The polymerization was carried out under the same conditions as in Example 5 except that the VDF feed amount was changed to 0.36 g, thereby obtaining a PTFE aqueous dispersion. The obtained PTFE aqueous dispersion had a solid content concentration of 29.8% by mass and an average primary particle size of 261 nm.

[0239] Using the obtained PTFE aqueous dispersion, a PTFE powder was obtained in the same manner as in Example 5. Various physical properties of the obtained PTFE powder were measured. The results are shown in Table 1.

[0240] Example 9

[0241] The polymerization was carried out under the same conditions as in Example 5 except that the VDF feed amount was changed to 2.1 g, the hydroquinone feed amount was changed to 18.0 mg, the stirring was stopped when the TFE feed amount reached 430 g, the pressure in the polymerization kettle was reduced to atmospheric pressure, TFE was introduced to make the pressure 2.7 MPaG, and the stirring was restarted. The obtained PTFE aqueous dispersion had a solid content concentration of 30.3% by mass and an average primary particle size of 226 nm.

[0242] Using the obtained PTFE aqueous dispersion, a PTFE powder was obtained in the same manner as in Example 5. Various physical properties of the obtained PTFE powder were measured. The results are shown in Table 1.

[0243] Example 10

[0244] The polymerization was carried out under the same conditions as in Example 5 except that VDF was changed to 0.52 g, ammonium persulfate (APS) was changed to 15.4 mg, the amount of hydroquinone fed was changed to 17.9 mg, and the final amount of TFE was changed to 1520 g at a polymerization pressure of 0.80 MPa and a polymerization temperature of 70° C., to obtain a PTFE aqueous dispersion. The obtained PTFE aqueous dispersion had a solid content concentration of 29.8% by mass and an average primary particle size of 278 nm.

[0245] Using the obtained PTFE aqueous dispersion, the coagulated wet powder was taken out in the same manner as in Example 5 and dried at 180° C. for 18 hours to obtain PTFE powder. Various physical properties of the obtained PTFE powder were measured. The results are shown in Table 1.

[0246] Embodiment 11

[0247] The polymerization was carried out under the same conditions as in Example 1 except that VDF was changed to 1.28 g of CTFE, the amount of potassium permanganate was changed to 3.87 mg, and the final amount of TFE was changed to 1790 g. A PTFE aqueous dispersion was obtained. The solid content concentration of the obtained PTFE aqueous dispersion was 33.0% by mass, and the average primary particle size was 263 nm.

[0248] Using the obtained PTFE aqueous dispersion, a PTFE powder was obtained in the same manner as in Example 1. Various physical properties of the obtained PTFE powder were measured. The results are shown in Table 1.

[0249] Example 12

[0250] Polymerization was carried out under the same conditions as in Example 1 except that VDF was changed to 2.60 g of CTFE and the final amount of TFE was changed to 1660 g to obtain a PTFE aqueous dispersion. The obtained PTFE aqueous dispersion had a solid content concentration of 31.4% by mass and an average primary particle size of 248 nm.

[0251] Using the obtained PTFE aqueous dispersion, a PTFE powder was obtained in the same manner as in Example 1. Various physical properties of the obtained PTFE powder were measured. The results are shown in Table 1.

[0252] Embodiment 13

[0253] Polymerization was carried out under the same conditions as in Example 5 except that VDF was changed to 0.11 g of HFP, ammonium persulfate (APS) was changed to 15.4 mg, the amount of hydroquinone fed was changed to 17.9 mg, and the final amount of TFE was changed to 1540 g at a polymerization pressure of 0.80 MPa and a polymerization temperature of 70° C., to obtain a PTFE aqueous dispersion. The obtained PTFE aqueous dispersion had a solid content concentration of 29.8% by mass and an average primary particle size of 312 nm.

[0254] Using the obtained PTFE aqueous dispersion, the coagulated wet powder was taken out in the same manner as in Example 5 and dried at 180° C. for 18 hours to obtain PTFE powder. Various physical properties of the obtained PTFE powder were measured. The results are shown in Table 1.

[0255] Comparative Example 1

[0256] The polymerization was carried out under the same conditions as in Example 1 except that the VDF feed amount was changed to 55.7 g and the potassium permanganate feed amount was changed to 4.46 mg to obtain a PTFE aqueous dispersion. The obtained PTFE aqueous dispersion had a solid content concentration of 33.1% by mass and an average primary particle size of 224 nm.

[0257] Using the obtained PTFE aqueous dispersion, a PTFE powder was obtained in the same manner as in Example 1. Various physical properties of the obtained PTFE powder were measured. The results are shown in Table 1.

[0258] Furthermore, a sample formed using the obtained PTFE powder in accordance with ASTM D 4895 was subjected to a heat treatment at 380° C. for 6 hours and then cooled to room temperature. As a result, severe foaming was found in the sample.

[0259] Comparative Example 2

[0260] Except that VDF was not added and the amount of white solid A was changed to 13 g, the amount of succinic acid was changed to 0.108 g, the amount of potassium permanganate was changed to 3.5 mg, and the final amount of TFE was changed to 1500 g, polymerization was carried out under the same conditions as in Example 1 to obtain a PTFE aqueous dispersion. The obtained PTFE aqueous dispersion had a solid content concentration of 29.5% by mass and an average primary particle size of 380 nm.

[0261] Using the obtained PTFE aqueous dispersion, a PTFE powder was obtained in the same manner as in Example 1. Various physical properties of the obtained PTFE powder were measured. The results are shown in Table 1.

[0262] [Table 1]

[0263]

[0264] Crack limit film thickness

[0265] About 5 ml of PTFE aqueous dispersion was dripped onto an aluminum plate of 20 cm long × 10 cm wide × 1.5 mm thick for flow coating, air dried with an inclined plate of about 80 degrees, dried at 110°C for 15 minutes, and fired at 380°C for 15 minutes to make a PTFE coating. The film thickness of the crack occurrence site confirmed by microscopic observation was measured using an eddy current film thickness meter (manufactured by Sunko Electronics Research Institute, SWT-9100). The average value of 10 points measured on each of the two coated plates was taken as the crack limit film thickness.

[0266] Embodiment 14

[0267] 3600g of deionized water, 180g of paraffin wax, and 1.18g of white solid A were added to a SUS reactor with a stirrer having a content of 6L. Next, the contents of the reactor were heated to 80°C while being sucked, and tetrafluoroethylene (TFE) was purged to remove oxygen in the reactor, and the contents were stirred. 5.82g of vinylidene fluoride (VDF) was pressed into the reactor with TFE, and then TFE was added to make it 2.70MPaG. An aqueous solution of 7.2mg of ammonium persulfate (APS) dissolved in deionized water was added to the reactor as an initiator. After the initiator was injected, a decrease in pressure occurred, and the start of polymerization was observed. TFE was added to the reactor, and the pressure was kept constant at 2.70MPaG. When the amount of TFE added reached 460g, an aqueous solution of 25.0mg of hydroquinone dissolved in the deionized water solution and a deionized water solution of 3.24g of white solid A were added. When the amount of TFE reaches about 1950 g, the supply of TFE is stopped, stirring is stopped, and the reaction is terminated. Afterwards, the pressure in the reactor is vented to normal pressure, nitrogen is replaced, and the contents are taken out of the reactor and cooled. Paraffin is removed to obtain a PTFE aqueous dispersion. The solid content concentration of the obtained PTFE aqueous dispersion is 35.3% by mass and the average primary particle size is 263 nm.

[0268] Pure water was added to the obtained aqueous dispersion and stirred at high speed to obtain wet PTFE powder. The obtained wet PTFE powder was dried at 150°C for 18 hours to obtain PTFE powder. The SSG of the obtained PTFE was 2.228 and the VDF content was 0.049% by mass.

[0269] 40 g of surfactant TDS-80 (manufactured by the First Industrial Pharmaceutical Company, polyoxyethylene alkyl ether) and 160 g of pure water were added to 1000 g of the obtained PTFE aqueous dispersion, and the mixture was allowed to stand at 70°C to obtain a PTFE aqueous dispersion concentrate having a PTFE resin solid content concentration of more than 65% by mass. Surfactant TDS-120 (manufactured by the First Industrial Pharmaceutical Company, polyoxyethylene alkyl ether) and pure water were added thereto to prepare a modified PTFE aqueous dispersion composition having a modified PTFE resin solid content concentration of 63% by mass and a surfactant amount of 5% by mass relative to the modified PTFE. The crack limit film thickness of the obtained modified PTFE aqueous dispersion composition was 4 μm.

Claims

1. A modified polytetrafluoroethylene having a breaking strength greater than 32.8N and a standard specific gravity greater than 2.

150.

2. The modified polytetrafluoroethylene according to claim 1, wherein The strength ratio represented by breaking strength (N) / extrusion pressure (MPa) was greater than 1.90 N / MPa.

3. The modified polytetrafluoroethylene according to claim 1 or 2, wherein: The breaking strength is greater than 37.0N.

4. The modified polytetrafluoroethylene according to any one of claims 1 to 3, wherein The standard specific gravity is 2.155 or above.

5. The modified polytetrafluoroethylene according to any one of claims 1 to 4, wherein The standard specific gravity is 2.160 or above.

6. A modified polytetrafluoroethylene having a standard specific gravity of 2.150 or more and a strength ratio represented by breaking strength (N) / extrusion pressure (MPa) of more than 1.90 N / MPa.

7. A modified polytetrafluoroethylene comprising tetrafluoroethylene units and vinylidene fluoride units, wherein the amount of the vinylidene fluoride units is 1.0% by mass or less based on all polymerized units.

8. The modified polytetrafluoroethylene according to any one of claims 1 to 7, which is in the form of powder.

9. The modified polytetrafluoroethylene according to any one of claims 1 to 8, which is in the form of fine powder. 10 . An aqueous dispersion comprising particles of the modified polytetrafluoroethylene according to claim 1 .

Citation Information

Patent Citations

  • Tetrafluoroethylene polymer having excellent strength

    JP2002201217A

  • Modified polytetrafluoroethylene and method for producing the same

    JP2006117912A

  • Tetrafluoroethylene fine powder and preparation thereof

    US4576869A

  • Polytetrafluoroethylene aqueous dispersion

    WO2021045228A1